Development and evaluation of a remotely controlled and monitored self-propelled sprayer in tomato crops - Penido, Édilus; Teixeira, Mauri; Fernandes, Haroldo; Monteiro, Paulo; Cecon, Paulo (Revista Ciência Agronômica, 2018)
The tomato is one of the main crops in Brazil. In large-scale cultivation, pesticides are applied to the plant to prevent the direct or indirect action of animal or vegetable life, aiming at higher productivity and better quality fruit. However, the products, if used incorrectly, may affect the health of workers involved in the activity. A prototype of a self-propelled sprayer, remotely controlled and monitored via radio signals, was therefore developed to be used in tomato crops, thus minimising worker contact with the chemical substances used when spraying. The basic prototype comprises an agricultural mini-tractor, a motorised pneumatic sprayer (atomiser) and a set of electronic and mechanical sensors and actuators, which allow the assembly to be controlled remotely and images captured by a video camera to be viewed on a tablet. After development, the principal dimension, weight and operational characteristics of the prototype were identified; the prototype was also used for spraying ten tomato plants in the crop, with seven different points being observed for each plant. The results were analysed statistically, giving the following coefficients of variation: 15.13% for spray coverage, 18.70% for droplet density and 16.68% for product deposition on the folioles. Based on these values, it was concluded that the development of a remotely controlled and monitored self-propelled sprayer prototype, and its use in spraying tomato crops, were viable.